Daytime Sleepiness, Poor Sleep Quality, Eveningness Chronotype and Common Mental Disorders Among Chilean College Students - Concepcion, Tessa (2014)
OBJECTIVES: To evaluate whether daytime sleepiness, poor sleep quality and morningness and eveningness preferences are associated with common mental disorders (CMDs) among college students. METHODS: A total of 963 college students completed self-administered questionnaires that collected information about socio-demographic characteristics, sleep quality characteristics, CMDs, and other lifestyle behaviors. RESULTS: The prevalence of CMDs was 24.3% (95% CI: 21.5-27.1%) among all students. Prevalence estimates of both excessive daytime sleepiness and poor sleep quality were higher among females (35.4% and 54.4%) than males (22.0% and 45.8%). Cigarette smoking was statistically significantly and positively associated with having CMDs (p=0.034). Excessive daytime sleepiness (OR= 3.65; 95% CI: 2.56-4.91) and poor sleep quality (OR=4.76; 95% CI: 3.11-7.29) were associated with increased odds of CMDs. CONCLUSION: Given the adverse health consequences associated with both sleep disorders and CMDs, improving sleep hygiene among college students is imperative to public health.